New statesman (New Statesman Ltd, 1996)
Irreverent, beautifully written and witty, the New Statesman is the essential read for bright thinkers everywhere. The magazine's award-winning team of editors and contributors seek to engage readers with great writing, arresting photography, intelligent analysis, bold campaigns and trenchant argument.
Keywords: Social sciences : Periodicals; Sciences sociales : Périodiques; Social conditions; Social sciences; Politiek; Maatschappij; Great Britain : Social conditions : Periodicals; Grande-Bretagne : Conditions sociales : Périodiques; Great Britain